Thermal Characteristics of Fireproof Plaster Compositions in Exposure to Various Regimes of Fire - Marina Gravit; Daria Shabunina; Sergey Antonov; Andrey Danilov (Buildings, 2022)
The problems of the fire safety of oil and gas facilities are particularly relevant due to the increasing complexity of technological processes and production. Experimental studies of steel structures with three different types of plasters are presented to determine the time taken to reach the critical temperature and loss of bearing capacity (R) of the sample, as a result of reaching a rate of deformation growth of more than 10 mm/min and the appearance of the ultimate vertical deformation. The simulation of the heating of steel structures showed a good correlation with the results of the experiment. The consumption of the plaster composition for the steel column was predicted, which allowed a 38% reduction in the consumption of fireproofing. It was found that to obtain the required fire resistance limit, it is necessary to consider the fire regime and apply plaster compositions with a thickness of 30–35 mm, depending on their thermal characteristics. The dependence of thermal conductivity and temperature on density is obtained, showing that the use of plaster compositions with a density of 200 to 600 kg/m3 is optimal to ensure a higher fire resistance limit. It is shown that the values of thermal conductivity of plaster compositions at 1000 °C are higher by 8–10% if the structure is exposed to a hydrocarbon fire regime. It is shown that the values of the heat capacity of plaster compositions at 1000 °C are higher by 10–15% if the structure is exposed to a standard fire regime.